Association of genetic variants in migraineurs with and without restless legs syndrome. Issue 10 (12th September 2020) - Lin, Guan‐Yu; Lin, Yu‐Kai; Liang, Chih‐Sung; Lee, Jiunn‐Tay; Tsai, Chia‐Lin; Hung, Kuo‐Sheng; Luo, Wen‐Jie; Tsai, Chia‐Kuang; Hsu, Yu‐Wei; Ho, Tsung‐Han; Yang, Fu‐Chi
Abstract: Objective: Several single‐nucleotide polymorphisms (SNPs) are associated with restless legs syndrome (RLS). This study investigated whether or not additional SNP variants increase the risk of RLS in migraineurs and in migraine with aura (MA) and migraine without aura (MoA) subgroups. Methods: Migraineurs with and without RLS were genotyped using an Affymetrix array. We performed association analyses for the entire cohort and the MA and MoA subgroups, which were divided further into episodic migraine (EM) and chronic migraine (CM). Potential correlations between SNPs and clinical indices in migraineurs with RLS were examined by multivariate regression analysis. Results: The rs77234324 and rs79004933 SNPs were found in migraineurs with ( P = 2.57E‐07) and without ( P = 3.03E‐07) RLS. The A allele frequency for rs77234324 (on LGR6 ) was 0.1321 in migraineurs with RLS and 0.0166 in those without RLS (odds ratio, 8.978). The T allele frequency for rs79004933 (in the intergenic region) was 0.1981 in migraineurs with RLS and 0.0446 in those without (odds ratio, 5.281). rs2858654, rs76770509, rs4243475 in UTRN, rs150762626, and rs2668375 were identified in migraine with and without RLS in the MoA subgroup ( P = 7.56E‐09, P = 2.30E‐08, P = 1.19E‐07, P = 6.86E‐07, and P = 8.05E‐07, respectively). There was a suggestion of an association between rs10510331 ( P = 1.50E‐06) and CM and EM in patients with MoA and RLS. Multivariate regression showed a significant relationship between rs79004933 and the Beck Depression Inventory score. Interpretation: rs77234324 in LGR6 and rs79004933 in the intergenic region were associated with RLS in migraineurs. Five SNPs increased the risk of RLS in patients with MoA.